2014
DOI: 10.1088/0964-1726/23/12/125009
|View full text |Cite
|
Sign up to set email alerts
|

Thermomechanical behavior of NiTiPdPt high temperature shape memory alloy springs

Abstract: Transformation strains in high temperature shape memory alloys (HTSMAs) are generally smaller than for conventional NiTi alloys and can be purposefully limited in cases where stability and repeatability at elevated temperatures are desired. Yet such alloys can still be used in actuator applications that require large strokes when used in the form of springs. Thus there is a need to understand the thermomechanical behavior of shape memory alloy spring actuators, particularly those consisting of alternative allo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 28 publications
(65 reference statements)
1
10
0
Order By: Relevance
“…Even though a wide range of NiTiPd alloys have been developed and studied over the years, they have not been fully exploited in engineering applications, but they have been considered for a few aerospace-related components [50][51][52][53][54]. Besides the high cost of Pd, the unsuccessful commercialization of this system is largely due to unresolved issues with dimensional/thermal stability, and lack of data concerning fatigue and durability, which are of prime importance to actuator applications at elevated temperatures (above 100 °C).…”
Section: Introductionmentioning
confidence: 99%
“…Even though a wide range of NiTiPd alloys have been developed and studied over the years, they have not been fully exploited in engineering applications, but they have been considered for a few aerospace-related components [50][51][52][53][54]. Besides the high cost of Pd, the unsuccessful commercialization of this system is largely due to unresolved issues with dimensional/thermal stability, and lack of data concerning fatigue and durability, which are of prime importance to actuator applications at elevated temperatures (above 100 °C).…”
Section: Introductionmentioning
confidence: 99%
“…The alloys produced by adding ternary elements, such as palladium (Pd), platinum (Pt), and gold (Au), to NiTi-based SMAs can widen the transformation temperature range to 100-800 • C [85,86]. Nicholson et al [87] studied the thermomechanical behavior of NiTiPdPt HTSMA springs. The authors observed that the transformation strains are generally smaller compared to conventional NiTi alloys.…”
Section: Characteristic Properties and Features Of Nitimentioning
confidence: 99%
“…2. Nicholson et al (2014) utilizes the full-form force-deflection equations to determine apparent shear modulus, G M , of the as-shape-set spring. This apparent shear modulus, G M , was then used to decouple the effects of geometry and material evolution before and after thermal cycling under constant load.…”
Section: Spring Actuatorsmentioning
confidence: 99%
“…reduced, modified, and/or full form) as the spring tool. The Ni 19.5 Ti 50.5 Pd 25 Pt 5 spring provided in Table 3 was used in Stebner et al (2009) and Nicholson et al (2014). The experimental results provided here are from Nicholson et al (2014).…”
Section: Spring Actuatorsmentioning
confidence: 99%
See 1 more Smart Citation